Use of Side Friction in Horizontal Curve Design: A Margin of Safety Assessment. Issue 1 (2016) - Donnell, Eric; Wood, Jonathan; Himes, Scott; Torbic, Darren
Current engineering practice uses a point-mass model to design horizontal curves on highways and streets. In this model, a maximum side friction factor is used, in combination with the selected design speed and maximum rate of superelevation, to determine the minimum radius of the curve for an alignment. The limiting value for side friction used in design was established in the 1940s and was based on driver comfort thresholds. The lateral friction available at the tire–roadway interface is a measure of friction supply and is dependent on the pavement surface type and condition, vehicle operating speed and deceleration characteristics, vehicle lane position, and tire type. The drivers' selection of individual operating speeds on a roadway results in a side friction demand when traversing a horizontal curve. The purpose of this paper is threefold. First, key side friction concepts in horizontal curve design are described. This description includes the definitions of and the fundamental principles associated with the application of side friction factors in horizontal curve design policy. Second, the paper provides an analysis of the margin of safety in horizontal curve design policy. This analysis considers various vehicle types, pavement surface types, and operating speed distributions, and makes comparisons between friction supply, demand, and design side friction factors. Third, the paper describes a framework for more effective consideration of the current vehicle fleet, range of pavement conditions, and vehicle speed distribution in horizontal curve design policy.